2022
DOI: 10.1002/ccd.30404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extracardiac vascular disease on outcomes of 1.4 million patients undergoing percutaneous coronary intervention

Abstract: Objectives Extracardiac vascular disease (ECVD) is increasingly recognized as a cardiovascular risk factor, but its association with outcomes after percutaneous coronary intervention (PCI) has not been well characterized. Methods Using the National Inpatient Sample database, all patients undergoing PCI between October 2015 and December 2018 were stratified by the presence and organ‐specific extent of extracardiac vascular comorbidity (cerebrovascular disease (CeVD), renovascular, aortic and peripheral arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…16 On the other hand, the increased risk of bleeding events of PAD patients is probably determined by the higher likelihood of periprocedural bleeding involving the vascular access and by the increased prevalence of some high-risk features such as advanced age or CKD, which affect not only ischemic but also bleeding risk. 1,5,6 We found that after adjustment for cardiovascular risk factors, comorbidities and CAD severity, the impact of PAD on ischemic and bleeding complications decreased and was no longer significant in both HBR and no-HBR patients. PAD remained an independent Of note, in some previous reports, PAD remained a significant predictor of adverse outcomes after adjustment 1,2 ; however, the endpoints' definitions and/or variables included in the adjusted models differed from our study.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…16 On the other hand, the increased risk of bleeding events of PAD patients is probably determined by the higher likelihood of periprocedural bleeding involving the vascular access and by the increased prevalence of some high-risk features such as advanced age or CKD, which affect not only ischemic but also bleeding risk. 1,5,6 We found that after adjustment for cardiovascular risk factors, comorbidities and CAD severity, the impact of PAD on ischemic and bleeding complications decreased and was no longer significant in both HBR and no-HBR patients. PAD remained an independent Of note, in some previous reports, PAD remained a significant predictor of adverse outcomes after adjustment 1,2 ; however, the endpoints' definitions and/or variables included in the adjusted models differed from our study.…”
Section: Discussionmentioning
confidence: 80%
“…Our results are consistent with previous studies that did not stratify patients according to the HBR status, which showed that PAD patients are at increased risk of both ischemic and bleeding complications after PCI, with the risk for ischemic events tending to be greater. 1,4,5,7,13 The accrued hazard of ischemic complications of PAD patients might be explained by the higher frequency of cardiovascular risk factors (e.g., advanced age, smoking or diabetes), 4,6,7 the elevated pro-inflammatory status 14,15 and the increased platelet reactivity. 16 On the other hand, the increased risk of bleeding events of PAD patients is probably determined by the higher likelihood of periprocedural bleeding involving the vascular access and by the increased prevalence of some high-risk features such as advanced age or CKD, which affect not only ischemic but also bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the Journal, Bashar et al 2 leveraged the National Inpatient Sample database, which is derived from all the states participating in the Healthcare Cost and Utilization Project (HCUP) and covers more than 97% of the US population. In this analysis, they included about 1.4 million patients undergoing PCI and evaluated in‐hospital outcomes in relation to the type of PAD as well as the number of vascular beds involved.…”
mentioning
confidence: 99%